Shear Strength Evaluation of Directly and Indirectly Loaded Rectangular Recycled Self-Compacted Reinforced Concrete Slender Beams Using Experimental and Finite Element Analysis - Alhussein, Thamer; Khudhairb, Jamal (University of Thi-Qar Journal, 2020)
This study presents an experimental and numerical evaluation of the shear behavior of recycled aggregate concrete beams without transversal reinforcement. These beams were manufactured as self-compacted concrete with the use of both natural aggregate and recycled aggregate. The beams were subjected to direct and indirect loading conditions. The mechanical properties of four mixes were characterized in terms of compressive strength, splitting tensile strength, and elastic modulus. The experimental results showed that the shear capacity of recycled aggregate concrete is lower than those made with natural aggregate. The experimental shear capacities of the tested beams were compared with ACI318M-14 and relevant research studies in the literature. The ratio of experimental shear stress divided by the root square of concrete compressive strength , which indicates the ability of diagonally cracked concrete to transmit tension and shear. was remained for all configurations greater than 0.17, which is the minimum value recommended by the ACI318-14. Results from nonlinear finite element models were compared with the experimental data, and good agreement was achieved